Technical skills measurement based on a cyber‐physical system for endovascular surgery simulation. Issue 3 (28th November 2012) - Tercero, Carlos; Kodama, Hirokatsu; Shi, Chaoyang; Ooe, Katsutoshi; Ikeda, Seiichi; Fukuda, Toshio; Arai, Fumihito; Negoro, Makoto; Kwon, Guiryong; Najdovski, Zoran
Abstract Background Quantification of medical skills is a challenge, particularly simulator‐based training. In the case of endovascular intervention, it is desirable that a simulator accurately recreates the morphology and mechanical characteristics of the vasculature while enabling scoring. Methods For this purpose, we propose a cyber‐physical system composed of optical sensors for a catheter's body motion encoding, a magnetic tracker for motion capture of an operator's hands, and opto‐mechatronic sensors for measuring the interaction of the catheter tip with the vasculature model wall. Two pilot studies were conducted for measuring technical skills, one for distinguishing novices from experts and the other for measuring unnecessary motion. Results The proficiency levels were measurable between expert and novice and also between individual novice users. The results enabled scoring of the user's proficiency level, using sensitivity, reaction time, time to complete a task and respect for tissue integrity as evaluation criteria. Additionally, unnecessary motion was also measurable. Conclusion The development of cyber‐physical simulators for other domains of medicine depend on the study of photoelastic materials for human tissue modelling, and enables quantitative evaluation of skills using surgical instruments and a realistic representation of human tissue. Copyright © 2012 John Wiley & Sons, Ltd.